Students’ Attitude towards the Utility of Kahoot! in English Learning: a Systematic Review - Al Haqqi, Kevin; Hesmatantya, Vega; Mayasari, Linda (Universitas Nahdatul Ulama Surabaya, 2023)
In the last three years till now, the use of online learning platforms significantly has become a trend caused by the pandemic. Many schools apply learning from home. It has been able to affect the students’ attitudes. Hence, teachers should think wisely about using the learning media. One of the popular online learning platforms, Kahoot!, is used by teachers. The impact of Kahoot! on students’ attitude is the researcher's concern. To support the research, the researcher applies a systematic review as research method. From a hundred articles, it has been filtered using a systematic review with PRISMA Flow into 38 articles obtained from Google Scholar, Garuda Ristekbrin, and Unpaywall. From 38 articles, it is able to state that Kahoot! is applied in learning all skills of English at once, writing skill, speaking skill, reviewing English, learning pronunciation skill, assessing vocabulary skill, conducting an exam of English, specific theme of English such as Events II, Recreation IV, Energy and Media, and tourism 1, grammar skill, reading skill, and vocabulary skill. Also, the students’ attitudes are mostly stated positive. The students are mostly motivated, better comprehending, excited, engaging, enjoyable, a good feeling, entertained, more active in class, paying attention, preferring the Kahoot!, and having the readiness to do with it in the next lesson. To recapitulate, the readers must be aware of common problems such as the internet and technical issues. Hence, the educators are able to keep the students’ attitudes in positive attitude.